Learning JavaScript in a local playground - Queirós, Ricardo (2019)
JavaScript is currently one of the most popular languages worldwide. Its meteoric rise is mainly due to the fact that the language is no longer bound to the limits of the browser and can now be used on several platforms. This growth has led to its increasing use by companies and, consequently, to become part of the curriculum in schools. Meanwhile, in the teaching-learning process of computer programming, teachers continue to use automatic code evaluation systems to relieve their timeconsuming and error prone evaluation work. However, these systems reveal a number of issues: they are very generic (one size fits all), they have scarce features to foster exercises authoring, they do not adhere to interoperability standards (e.g. LMS communication), they rely solely on remote evaluators being exposed to single point of failure problems and reducing application performance and user experience, which is a feature well appreciated by the mobile users. In this context, LearnJS is presented as a Web playground for practicing the JavaScript language. The system uses a local evaluator (the user’s own browser) making response times small and thus benefiting the user experience. LearnJS also uses a sophisticated authoring system that allows the teacher to quickly create new exercises and aggregate them into gamified activities. Finally, LearnJS includes universal LMS connectors based on international specifications. In order to validate its use, an evaluation was made by a group of students of Porto Polytechnic aiming to validate the usability of its graphical user interface.